I can do it, so can you: The role of leader creative self-efficacy in facilitating follower creativity - Huang, Lei; Krasikova, Dina V.; Liu, Dong (Organizational behavior and human decision processes, 2016)
•We study the role of leader creative self-efficacy (LCSE) in follower creativity.•LCSE is positively related to leader encouragement of creativity (LEC).•Follower creative process engagement (FCPE) is related to follower creativity.•Leader–member exchange (LMX) strengthens the positive effect of LEC on FCPE.•LMX boosts the effect of LCSE on follower creativity via LEC and FCPE. Creativity scholars have long called for more research on the effects of leader characteristics on employee creativity. Answering this call, this study draws on social cognitive theory to examine the effect of leader creative self-efficacy (CSE) on follower creativity. Using a sample of 544 employees nested under 106 supervisors at a large information technology company in the U.S., we obtained support for the indirect effect of leader CSE on follower creativity via leader encouragement of creativity and follower creative process engagement. In addition, follower leader–member exchange (LMX) strengthened the relationship between leader encouragement of creativity and follower creative process engagement. Thus, in the presence of higher LMX, leader CSE is likely to have a stronger positive impact on employee creativity through leader encouragement of creativity and, subsequently, follower creative process engagement. Our findings contribute to a better understanding of the role of leader attributes in employee creativity.